An 18-year Study of Malignant Melanoma in Childhood and Adolescence. Issue 8 (August 2019) - Al-Himdani, Sarah; Naderi, N.; Whitaker, I.S.; Jones, N.W.
Abstract : Background: Malignant melanoma is rare in childhood and adolescence. Diagnostic uncertainty and misdiagnosis often lead to delayed treatment. Methods: We evaluated children and adolescents under 20 years of age presenting with malignant melanoma at our institution over an 18-year period. Data were collected, analyzed, and interpreted, following which findings were compared with the existing literature. Results: Twenty-four patients were included in the study with mean follow-up of 61.8 months. Males comprised 54% of cases. On presentation, 33% of children had melanoma of s thickness 2–4 mm and 34% had stage III disease. Younger children presented with thicker melanomas, differing subtypes, and more advanced stage disease compared with older children. Extremities were the most common sites affected (42%). Dissection of the draining lymph node basins was undertaken in 38% of cases. Overall survival was 92%. Conclusions: Tumor subtype, biology, hormonal influence, and lymph node status are all important prognostic factors in malignant melanoma in childhood and adolescence. Compared with adults, children presenting with thicker melanomas and more advanced stage disease generally have more favorable outcomes and a better survival. Plastic surgeons, commonly encountering skin lesion in children, must maintain a high index of suspicion so that early excision and sentinel lymph node biopsy may be promptly offered to patients with melanoma.